Roles of Three HSF Domain-Containing Proteins in Mediating Heat-Shock Protein Genes and Sustaining Asexual Cycle, Stress Tolerance, and Virulence in Beauveria bassiana - Zhou, Gang; Ying, Sheng-Hua; Hu, Yue; Fang, Xiang; Feng, Ming-Guang; Wang, Jie (Frontiers in Microbiology, 2018)
Heat shock transcription factors (HSFs) with a HSF domain are regulators of fungal heat shock protein (HSP) genes and many others vectoring heat shock elements (HSEs), to which the domain binds in response to heat shock and other stress cues. The fungal insect pathogen Beauveria bassiana harbors three HSF domain-containing orthologous to Hsf1, Sfl1 and Skn7 in many fungi. Here we show that the three proteins are interrelated at transcription level, play overlapping or opposite roles in activating different families of 28 HSP genes and mediate differential expression of some genes required for asexual developmental and intracellular Na+ homeostasis. Expression levels of skn7 and sfl1 largely increased in hsf1, which is evidently lethal in some other fungi. Hsf1 was distinct from Sfl1 and Skn7 in activating most HSP genes under normal and heat-shocked conditions. Sfl1 and Skn7 played overlapping roles in activating more than half of the HSP genes under heat shock. Each protein also activated a few HSP genes not targeted by two others under certain conditions. Deletion of sfl1 resulted in most severe growth defects on rich medium and several minimal media at optimal 25ºC while such growth defects were less severe in hsf1 and minor in skn7. Conidiation level was lowered by 76% in skn7, 62% in sfl1 and 39% in hsf1. These deletion mutants also showed differential changes in cell wall integrity, antioxidant activity, virulence and cellular tolerance to osmotic salt, heat shock and UV-B irradiation. These results provide a global insight into vital roles of Hsf1, Sfl1 and Skn7 in B. bassiana adaptation to environment and host.